$$\sum_{n=1}^{\infty}\frac{1}{n^s}\sum_{n=1}^{\infty}\frac{\mu(n)}{n^s}=1$$ for $s>1$.

How do I prove this identity?


The idea needed here is Dirichlet convolution.

The convolution identity states that if

$$\left(\sum_{j=1}^\infty \frac{a_j}{j^s}\right)\left(\sum_{k=1}^\infty \frac{b_k}{k^s}\right)=\sum_{\ell=1}^\infty \frac{c_\ell}{\ell^s}$$


$$\sum_{k\,\mid \,n} a_k b_{n/k} = c_n$$

where the sum ranges over all positive divisors of $n$.

More specifically, your original identity is equivalent to the convolution identity

$$\sum_{k\,\mid \,n} \mu(k) = [n=1]$$

where the two functions being convolved are the constant function $1$ and the Möbius function $\mu(k)$. ($[p]$ here is the Iverson bracket; it evaluates to $1$ if $p$ is true, and $0$ if $p$ is false.)

For $n=1$, the identity is easily verified. To see what happens when $n > 1$, take the prime factorization

$$n=\prod_{k=1}^r p_k^{m_k}$$

It is known that the summatory function of a multiplicative function is itself multiplicative; thus, letting $\xi(n)=\sum\limits_{k\,\mid \,n} \mu(k)$, we have $\xi(qr)=\xi(q)\xi(r)$. We can thus restrict to the case


and since $\xi(n)=\xi(p_1^{m_1})\xi(p_2^{m_2})\cdots \xi(p_r^{m_r})$, $\xi(n)=0$ for $n > 1$.

  • $\begingroup$ I was wondering how to show that "The Dirichlet series that generates the Möbius function is the (multiplicative) inverse of the Riemann zeta function." $\endgroup$ – Kou Nov 20 '11 at 2:45
  • $\begingroup$ Right; remember that the Dirichlet coefficients of the product of two Dirichlet series is the Dirichlet convolution of the Dirichlet coefficients of the individual series. $\endgroup$ – J. M. is a poor mathematician Nov 20 '11 at 3:03

Let $D_f(s)$ denote the Dirichlet generating series:

$$ D_f(s) = \sum_{n =1}^{\infty} \frac{f(n)}{n^s}. $$

When the series convergences absolutely, we can write $D_f(s)$ as an Euler product:

$$ D_f(s) = \prod_p \left(1+f(p)p^{−s} +f(p^2)p^{−2s} \dots \right) $$ where the product ranges over all the primes $p$. Looking at the Euler product for $\zeta(s)$ (which corresponds to $f(n) = 1$) we see that

$$ \zeta(s) = \prod_p \left(1+p^{-(s-1)} +p^{-2(s-1)}+ \dots \right) = \prod_p \left(1 - p^{-s} \right)^{-1}. $$


$$\begin{align} \frac{1}{\zeta(s)} = \prod_{p} \left(1 - p^{-s} \right) = \sum_{n=1}^{\infty} \frac{g(n)}{n^s}, \end{align}$$

where $g$ is the multiplicative function such that $g(p) = -1$, and $g(p^n) = 0$ when $n \geq 2$. Note that this is precisely the definition of $\mu$ (and this is probably how the formula for $\mu$ was originally discovered). Thus, we have shown that:

$$ \sum_{n=1}^{\infty} \frac{1}{n^s} \cdot \sum_{n=1}^{\infty} \frac{\mu(n)}{n^s} = \zeta(s) \cdot \frac{1}{\zeta(s)} = 1$$

which is valid when $\zeta(s)$ converges absolutely (so this is valid for $s = \sigma + it \in \mathbb{C}$ such that $\sigma > 0$).


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.